Relationship dynamics and behavioral adaptations in the control of the 2022 mpox epidemic - Ulrik Hvid; Lone Simonsen; Morten Frisch; Kim Sneppen (Proceedings of the National Academy of Sciences, 2025)
We analyzed the patterns of transmission in the 2022 clade IIb mpox epidemic as it unfolded in the European population of men who have sex with men (MSM). We developed an agent-based model that simulates sexual pair formation, incorporating both brief and longer-term sexual relationships. The model implements survey data on the sexual behavior of MSM and accounts for the highly heterogeneous nature of the sexual contact network within this community. When simulating the mpox epidemic, the model reproduces the reported numbers of sexual partners of mpox-infected individuals. We find that infection-derived immunity had little impact on ending the European outbreak. Instead, we suggest that the marked decrease in serial interval observed across the epidemic reflects a substantial increase in self-isolating behavior among infected persons and that this is sufficient to explain the early control of the epidemic. Our work highlights the critical interplay between relationship dynamics and adaptive behaviors in shaping mpox epidemic patterns and achieving control in 2022. Despite continued propagation of clade IIb mpox, the European MSM population remains protected by immunity, primarily vaccine-induced.